Women in Peacebuilding: Afghan Women’s Struggles Against Intersectional Oppression during Peace Negotiations - Akhmady, Fajarningrum; Rahmawati, Nursabrina; Krisnamukti, Tedy Asjad (Journal of Feminism and Gender Studies, 2026)
The drastic changes in Afghanistan's social and political structure following the Taliban's takeover of the government in 2021 have resulted in severe oppression of women. The reimplementation of discriminatory policies has created significant challenges for Afghan women in fighting for their rights. This study aims to analyze women's struggles within the context of peace negotiations, not only in the Doha Agreement between the United States and the Taliban; which failed to address women’s rights, but also in the subsequent intra-Afghan negotiations between the Taliban and the Afghan government, where women continued to face structural barriers to meaningful participation. Using a postcolonial feminist approach, this research explores the concept of "double colonization" experienced by Afghan women, where they are caught between Taliban oppression and neglect by the US. The findings reveal that while women actively engage through organizations and activism to participate in the peace process, their voices are often ignored by multiple layers of oppression. Women's participation in intra-Afghan talks remains minimal, and peace agreements do not guarantee the protection of their fundamental rights. This study underlines the importance of women's inclusion in the peace negotiation process to ensure peace for women in the form of fulfillment of rights and security after a peace agreement is reached between the conflicting parties.